Towards carbohydrate recognition in aqueous media - Ryan, Theo J. (Trinity College (Dublin, Ireland). School of Chemistry, 2002)
Chapter One provides a brief introduction to supramolecular chemistry. The types of interactions involved in host-guest chemistry are discussed as well as the principles behind the design of a receptor. Chapter Two examines carbohydrate recognition in organic media. Contributions from various laboratories including the Davis laboratory provide a variety of receptors with different carbohydrate binding abilities. Chapter Three describes the phenomena of carbohydrate recognition in aqueous media. Contributions within this area from various laboratories are described, as well as the aims of this project. Chapter Four gives an account of the synthesis of the pentyl macrotricycle 2.57 as previously carried out by Wareham. Improvements made to this synthesis are described in detail. Chapter Five relates the syntheses of two new organic-soluble macrotricyclic receptors, namely benzyl macrotricycle 5.6 and polybenzyl macrotricycle 5.17. Also discussed is the synthesis of the water-soluble macrotricycle 5.23. Chapter Six details testing carried out on the pentyl macrotricycle 2.57 by means of 1H magic angle spinning NMR on a solid supported glucoside. Also described are 1H NMR binding studies of polybenzyl macrotricycle 5.17 for octyl- β-D-glucoside in various solvents as well as the extraction of various carbohydrates from aqueous into organic media by 5.17. Chapter Seven is a detailed account of the experimental procedures for the syntheses of the reported compounds.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin